Synthesis of a novel axially substituted silicon phthalocyanine sensitizer for efficient singlet oxygen generation by comparing PDT and SPDT studies - Kose, Gulsah Gumrukcu; Karaoglan, Gulnur Keser (ELSEVIER, 2023)
This study is based on photodynamic therapy (PDT) and sonophotodynamic therapy (SPDT) which combines photochemical and sonochemical studies, produces high singlet oxygen and provides more effective therapeutic results in the treatment of cancer. For this purpose, a new photosensitizer, naphthoic acid substituted silicon phthalocyanine, is synthesized and characterized by elemental analysis, 1H NMR, FT-IR, MALDI-TOF MS and UV-Vis spectral data and its photophysico-chemical properties are investigated. The singlet oxygen quantum yields that were obtained by photochemical and sono-photochemical methods of the complex, synthesized as a sono-photosensitizer, were calculated and compared by both methods. It was observed that the yield obtained in the sono-photochemical method (CYRILLIC CAPITAL LETTER EF Delta = 0.74 in DMSO, 0.69 in DMF) was considerably higher than the one obtained in the photochemical method (CYRILLIC CAPITAL LETTER EF Delta = 0.51 in DMSO, 0.47 in DMF). These results proved that sonophotochemical study remarkably increased the therapeutic effect which is important in cancer treatment.
Keywords: Silicon (IV) phthalocyanine; Photodynamic therapy; Sono-photodynamic therapy; Singlet oxygen; Sensitizer; PHOTOCHEMICAL PROPERTIES; ZINC PHTHALOCYANINE; SONODYNAMIC THERAPY; PHOTOPHYSICAL PROPERTIES; RECENT PROGRESS; IN-VITRO; CANCER; EFFICACY; SOLVENT; Chemistry; Physics